Yoga reduces chronic low back pain: An innovative approach - Jalandhara Bhatta; Padmini Tekur; Sham Ganpat Tikhe; Hongasandra Ramarao Nagendra (Wolters Kluwer Medknow Publications, 2015)
Background: Although yoga is an effective treatment for chronic low back pain (CLBP), little is known about the mechanisms responsible for its benefits. Objective: To study the effect of Integrated Approach of Yoga Therapy (IAYT) on disability, depression, and pain in patients with CLBP. Method: Seven days intensive residential IAYT program in a single group pre-post study was conducted in a holistic health centre at Bengaluru, India. Thirty-five patients (22 females, 13 males) with CLBP were selected conveniently to undergo the IAYT program. The IAYT program was a combination of Asanas (physical postures), Pranayama (breathing practices), and meditation, apart from interactive sessions on the philosophical concepts of yoga. The modified Roland-Morris Disability Questionnaire (RMDQ), Beck Depression Inventory (BDI), and Straight Leg Raising (SLR) Test were administered before and after the IAYT program. Statistical Analysis: The Statistical Package for the Social Sciences version 16 was used for statistical analysis. The Shapiro-Wilk test showed that the data was normally distributed. Paired samples t-test was used to compare the means. Results: The data analysis showed significant change (p< 0.001, in all cases) with 54.13% decrease in the RMDQ scores (t = 0.759), 36.46% increase in right (t = 0.887) and 36.04% (t = 0.884) in left SLR scores, and 71.47% decrease in BDI scores (t = 0.797). Conclusion: The present study suggests that 7-day intensive residential IAYT program reduces disability and depression and improves spinal mobility in patients with CLBP. Thus, yoga may play a vital role in the management of CLBP. Additional randomized control trials are needed before a strong recommendation can be made.